2005
DOI: 10.1128/jvi.79.22.14297-14308.2005
|View full text |Cite
|
Sign up to set email alerts
|

O Mannosylation of α-Dystroglycan Is Essential for Lymphocytic Choriomeningitis Virus Receptor Function

Abstract: ␣-Dystroglycan (␣-DG) was identified as a common receptor for lymphocytic choriomeningitis virus (LCMV) and several other arenaviruses including the human pathogenic Lassa fever virus. Initial work postulated that interactions between arenavirus glycoproteins and ␣-DG are based on protein-protein interactions. We found, however, that susceptibility toward LCMV infection differed in various cell lines despite them expressing comparable levels of DG, suggesting that posttranslational modifications of ␣-DG would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 56 publications
7
53
0
Order By: Relevance
“…An important role for glycosylation for the function of ␣-DG as an LCMV receptor comes independently from the observation that cells deficient in the biosynthesis of ␣-DG's O-mannosyl glycans are less susceptible to viral infection (29).…”
Section: Discussionmentioning
confidence: 99%
“…An important role for glycosylation for the function of ␣-DG as an LCMV receptor comes independently from the observation that cells deficient in the biosynthesis of ␣-DG's O-mannosyl glycans are less susceptible to viral infection (29).…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) 83.6 (anti-LCMV GP2) and 113 (anti-LCMV NP) were described previously (9, 51), as were anti-␣-DG mAb IIH6 (18) and GT20ADG polyclonal antibody (4 (41). The O-mannosylation-deficient cell lines Lec15.2 and Lec35 were maintained as described previously (24), and the mutant line psg〈-745 was maintained as outlined previously (41). DG ϩ/Ϫ and DG Ϫ/Ϫ embryonic stem (ES) cells were maintained as described previously (22).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies reported a critical role for protein O mannosylation in the infection of cells with different LCMV isolates (24). Independently, LARGE-dependent modification was also found to be crucial for arenavirus binding (29).…”
mentioning
confidence: 99%
“…The fact that M. leprae and viruses bind to the native protein but not to recombinant forms indicates that glycosylation is likely to be essential in infection (Cao et al, 1998;Rambukkana et al, 1998). Specifically, O-mannosylation and post-translational modification of ␣-dystroglycan by the putative glycosyltransferase LARGE is crucial for its action as a cellular receptor for viruses (Imperiali et al, 2005;Kunz et al, 2005). Defects in glycosylation pathways cause numerous human diseases, such as the well-characterized congenital disorders of glycosylation (CDGs), which is a group of multisystemic syndromes that particularly affect the central nervous system (Jaeken and Carchon, 2004).…”
Section: Dystroglycan Interactionsmentioning
confidence: 99%